The First High‐Pressure Chromium Oxonitridoborate CrB4O6N—an Unexpected Link to Nitridosilicate Chemistry. Issue 40 (31st August 2021) - Fuchs, Birgit; Johrendt, Dirk; Bayarjargal, Lkhamsuren; Huppertz, Hubert
Abstract: CrB4 O6 N crystallizes in the non‐centrosymmetric space group P 63 mc (no. 186) with the lattice parameters a =5.1036(1), c =8.3519(3) Å, and a volume of 188.40(1) Å 3 . It was synthesized in a high‐pressure/high‐temperature experiment at 7 GPa and 1673 K and represents the first high‐pressure oxonitridoborate. It is built up of starlike‐shaped entities of four BO3 N tetrahedra, connected via one common nitrogen atom that resembles the fourfold‐coordinated nitrogen atoms in the homeotypic nitridosilicates MYbSi4 N7 (M=Sr, Ba). Building up a network with channels that contain the Cr 3+ ions, CrB4 O6 N contains for the first time a tetrahedral building unit in contrast to trigonal planar B(O/N)3 entities in all other known oxonitridoborates. The structural relations as well as the results of spectroscopic measurements and calculations on the chromium oxonitridoborate are discussed. Abstract : Through a high‐pressure/high‐temperature approach, CrB4 O6 N could be obtained as the first oxonitridoborate containing BO3 N tetrahedra and building up a 3D framework. In contrast to other members of this substance class, the nitrogen atoms connect four boron atoms. Homeotypes can be found in the nitridosilicates M YbSi4 N7 ( M =Sr, Ba, Eu), which were the first to feature this fourfold connected nitrogen atoms.